UJI AKTIVITAS EKSTRAK ETANOL 70% DAUN BAWANG DAYAK (Eleutherine palmifolia, (L.) Merr) TERHADAP PERTUMBUHAN Candida albicans - Eka Kumalasari; Suci Renita; Dwi Rizki Febrianti; Rakhmadhan Niah (Jurnal Insan Farmasi Indonesia, 2021)
Eleutherine palmifolia (L.) Merr. Is one of the typical Central Kalimantan plants that has been hereditary used by Dayak people as traditional medicine. Generally, only parts of dayak onion bulbs are used while the onion leaves are often discarded and rarely used. Dayak onion leaves contain chemical compounds that are efficacious as antimicrobials namely alkaloids, flavonoids, saponins, phenols, tannins, triterpenoids and steroids.This type of research is experimental. Using the paper disc diffusion. The purpose of this study was to determine the antifungal activity of 70% ethanol extract of onion leaves on the growth of albicans candida fungi. Eleutherine palmifolia (L.) Merr leaves originating from the Palagka Raya City area of ??Central Borneo. The sample in this study was 70% ethanol extract. The results of this study can be concluded that 70% ethanol extract of dayak onion leaves has activity on the growth of Candida albicans. The diameter of the inhibitory zone in 70% ethanol extract of dayak onion leaves was obtained at a concentration of 100% 21.6 mm, a concentration of 80% 17.45 mm, a concentration of 60% 13.35 mm, a concentration of 40% 10.67mm, concentration 20% 8.35 mm.